Multiple sclerosis : bench to bedside : global perspectives on a silent killer - Asea, Alexzander A. A.; Geraci, Fabiana; Kaur, Punit (Springer, 2017)
"Multiple Sclerosis (MS) is one of the main causes of disability in young adult population. The estimated burden of the disease worldwide is about three million people. The pathogenic mechanism of MS involves both auto immune and degenerative processes. These two mechanisms are thought to determine a combination of events leading to several clinical pattern of disease onset and course. Multiple Sclerosis: Bench to Bedside provides the most up-to-date and concise reviews on the critical issues of multiple sclerosis from around the world. This book is written by leaders and experts in the field of multiple sclerosis research and is divided into easy to read sections. Section I focuses on basic science aspects of Multiple Sclerosis, including potential biomarkers, molecular biology, heat shock proteins, oxidative stress, genetic and epigenetics. Section II focuses on clinical and epidemiological aspects of Multiple Sclerosis, including remyelination therapy, neuroplasticity-based technologies and interventions. This is an important reference book and a must-read for Postgraduate Medical Scholars, Basic Science Researchers and Neurologists in Clinical Practice"- Resumé vydavatel
Keywords: roztroušená skleróza; multiple sclerosis; elektronické knihy; kolektivní monografie; electronic books; collective monographs